Effect of UV Irradiation on Interactions of α-Lipoic Acid with Free Radicals - Paweł Ramos; Piotr Pepliński; Barbara Pilawa (International Journal of Photoenergy)
Changes of antioxidant properties of α-lipoic acid (LA) after UV irradiation were studied. LA is the typical drug used in diabetic neuropathy. Quenching of free radicals is an important factor of therapy by using this substance. α-Lipoic acid is exposed to UV irradiation during the storage. The aim of our studies was to examine the effect of UV irradiation on the interactions of LA with free radicals. The α-lipoic acid was irradiated by UVA 315–400 nm light during 10 to 110 minutes by intervals of 10 minutes. The electron paramagnetic resonance spectroscopy was used as the experimental technique. The antioxidant properties of LA were spectroscopically confirmed. The strong effect of UV irradiation on interactions of α-lipoic acid with free radicals was observed. It was pointed out that interactions of LA with free radicals decrease after its exposition on UV. The interactions of LA with free radicals were higher after the sample irradiation during 10 minutes than for the samples irradiated longer (20–110 minutes). The results are important for problems connected with photomedicine; they pointed out that α-lipoic acid should not be stored on UV exposition. Application of electron paramagnetic resonance spectroscopy to characterize interactions of pharmacological substance with free radicals was confirmed.